Koreksi gigitan terbalik posterior dan anterior dengan alat cekat rapid maxillary expansion dan elastik intermaksila - Retno Dewati; Teguh Budi Wibowo; Masyithah Masyithah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: Children with anterior and posterior crossbite usually have a complaint in aesthetic and masticatory function. It could caused by bad habits and hereditary factors which made worse condition. Purpose: The purpose of this case report was to report the use of orthodontic appliance rapid maxillary expansion (RPE) and intermaxillary elastic to correct posterior and anterior crossbite in teenage patient. Case: A fourteen years-old teenage female patient came to Dental Hospital Dentistry Universitas Airlangga with case of anterior posterior cross bite and unerupted permanent teeth. Case management: The case was treated using orthodontic fixed appliance rapid maxillary expansion (RPE) and followed by intermaxillary elastics. The posterior cross bite treatment took 4 weeks used of orthodontic fixed appliance RPE, while, treatment of anterior cross bite which used intermaxillary elactic was done within three month to achieved normal occlusion. Conclusion: This case report showed that the orthodontic appliance rapid maxillary expansion (RPE) and intermaxillary elastic could be used to correct posterior and anterior crossbite.Latar belakang: Anak dengan gigitan terbalik anterior dan posterior pada umumnya mempunyai keluhan dalam hal estetik dan fungsi pengunyahan. Kondisi gigitan terbalik biasanya disebabkan oleh adanya kebiasaan buruk dan faktor keturunan yang semakin memperparah keadaan tersebut. Tujuan: Laporan kasus ini melaporkan pemakaian alat cekat rapid maxillary expansion (RPE) dan elastik intermaksila untuk mengkoreksi gigitan terbalik posterior dan anterior pada anak remaja. Kasus: Pasien remaja perempuan berusia 14 tahun datang ke Rumah Sakit Gigi dan Mulut Fakultas Kedokteran Gigi Universitas Airlangga Surabaya dengan kasus gigitan terbalik anterior posterior dan terdapat gigi permanen yang tidak tumbuh. Tatalaksana kasus: Perawatan yang dilakukan adalah koreksi gigitan terbalik dengan menggunakan alat ortodonsia cekat rapid maxillary expansion (RPE) dan dilanjutkan dengan pemasangan elastik intermaksila. Perawatan koreksi gigitan terbalik posterior memerlukan waktu 4 minggu menggunakan alat ortodonti cekat RPE, sedangkan koreksi gigitan terbalik anterior dilakukan dalam 3 bulan untuk mencapai oklusi normal. Simpulan: Laporan kasus ini menunjukkan bahwa pemakaian alat cekat rapid maxillary expansion (RPE) dan elastik intermaksila dapat mengkoreksi gigitan terbalik posterior dan anterior.